PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT CESCO LOGISTIK INDONESIA - Kaida, Nur; Dja'far, Abu Bakar (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the positive and significant influence of leadership style and work environment variables on employee performance at PT Cesco Logistik Indonesia Jakarta. The sample used was a saturated sampling technique, totaling 50 employees. Data analysis techniques use descriptive analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and f test. Simultaneous research results show a positive and significant influence between leadership style and work environment on employee performance at PT Cesco Logistik Indonesia Jakarta, this can be proven from the multiple linear regression equation Y = 7.991+ 0.130 X1 + 0.361 X2, correlation value of 0.551, the coefficient of determination value is 30.3% and the value of Fcount > Ftable (22,409 > 3.20) this is also reinforced by the p value < 0.05).